أشكال تمويل مي ا زنية البلدية في القانون الج ا زئري - حياة, مسعي; ربيعة, بو ا ربح; طراد, سليم (My University, 2023)
إن التحول في حياة وفلسفة الدول والميل نحو التوسع في التطبيق الديمق ا رطي لنظم الإدارة المحلية لإدارة تحديات التنمية المحلية، هو اتجاه لا يمكن تجاهله في العصر الحديث، كما أن تعميق هذا المفهوم لا يمكن أن يتم إلا من خلال المحاولات الجادة عبر فت ا رت زمنية لتطوير نظم الإدارة المحلية، ليجسد هذا النظام أداة الدولة في تحقيق رفاهية المجتمع المحلي. يعني هذا مزيدا من اللامركزية الإدارية وحرية أكبر في تسيير الشؤون المحلية وهذا بطبيعة الحال يتطلب استقلالية مالية وموارد ذاتية تواجه بها الجماعات المحلية نفقاتها الخاصة، وهو الأمر الذي تفتقده معظم البلديات الج ا زئرية واجهت عج ا ز ماليا في مي ا زنيتها أي أن نفقاتها لم تكفي لتغطية إي ا رداتها، يرجع هذا لجملة من الأسباب مباشرة وغير مباشرة، الأمر الذي يوجب القيام بمجموعة من الإصلاحات تدور في مجملها حول ترشيد النفقات البلدية وتثمين الإي ا ردات ومعالجة اختلالات النظام الجبائي الحالي والاهتمام بالموارد البشرية، ومن شأن هذا أن يكون بمثابة وصفة ناجعة لمعالجة اختلال مي ا زنية البلديات أو على الأقل التخفيف من حدة الداء.The transformation in the life and philosophy of states and the tendency towards expanding the democratic application of local administration systems to manage the challenges of local development is a trend that cannot be ignored in the modern era, and the deepening of this concept can only be done through serious attempts over time periods to develop local administration systems. This system embodies the state's tool in achieving the welfare of the local community. This means more administrative decentralization and greater freedom in the conduct of local affairs, and this naturally requires financial independence and self-resources with which local groups face their own expenses, which is something that most Algerian municipalities lack. They faced a financial deficit in their budget, meaning that their expenditures were not sufficient to cover their revenues. There are direct and indirect reasons, which necessitates carrying out a set of reforms that revolve in their entirety around rationalizing municipal expenditures, valuing revenues, addressing imbalances in the current fiscal system, and paying attention to human resources.
مذكرة ماستر
Keywords: مي ا زنية– مصادر ذاتية- قانون – البلدية.; budget - self-resources - law – municipality.